Characterization of a novel Morganella morganii bacteriophage FSP1 isolated from river water. Issue 2 (28th August 2014) - Yamaki, Shogo; Omachi, Takuo; Kawai, Yuji; Yamazaki, Koji
Abstract Morganella morganii has been identified as a causative agent of opportunistic infections and histamine poisoning. Bacteriophage is a virus and has recently been considered an alternative agent to antibiotics for the control of bacteria that have developed antibiotic resistance. In this study, a novel M. morganii bacteriophage isolated from river water was characterized. The isolated phage, termed FSP1, was purified by polyethylene glycol precipitation followed by cesium chloride density‐gradient centrifugation. FSP1 has infectivity against only M. morganii and was identified as a Myoviridae bacteriophage through morphological analysis with transmission electron microscopy. According to the one‐step growth curve, the FSP1 latent period, eclipse period, and burst size were 30, 20 min, and 42 PFU infected cell−1, respectively. The genome size of FSP1 was estimated to be c. 45.6–49.4 kb by restriction endonuclease analyses. Moreover, challenge testing against M. morganii in vitro revealed that FSP1 had high lytic activity and that the viable cell count of M. morganii was reduced by 6.12 log CFU mL−1 after inoculation with FSP1 at a multiplicity of infection (MOI) = 10. These results suggested that FSP1 could be used as a biocontrol agent against M. morganii for treatment of infectious disease treatment or food decontamination.